EuNi2P4, the first magnetic unconventional clathrate prepared via a mechanochemically assisted route. Issue 5 (23rd January 2020) - Plokhikh, Igor V.; Khan, Nazir; Tsirlin, Alexander A.; Kuznetsov, Alexey N.; Charkin, Dmitri O.; Shevelkov, Andrei V.; Pfitzner, Arno
Abstract : The first magnetic unconventional clathrate EuNi2 P4 has been prepared and its thermodynamic properties have been investigated. Abstract : For the first time, a magnetic unconventional clathrate EuNi2 P4 has been prepared from the elements via a combined mechanochemical and solid-state route. Its crystal and electronic structure, magnetic and transport properties as well as lattice dynamics were elucidated. It crystallizes in the orthorhombic space group Fddd ( Z = 8) with unit cell parameters a = 5.1852(1) Å, b = 9.4834(1) Å, and c = 18.9893(2) Å, V = 933.78(1) Å 3 at room temperature. Its crystal structure can be described as a covalent Ni–P framework forming a twisted Kelvin cell with Eu 2+ guest cations occupying the voids of this framework, which is supported by chemical bonding analysis based on the electron localization function topology. Eu 2+ guests sit inside the oversized cages with a coordination number of 24 and exhibit strong rattling, which manifests in both thermodynamic properties and Raman spectra. The compound is metallic and exhibits a rather low thermal conductivity of ∼4 W K −1 m −1 at high temperature along with a positive Seebeck coefficient. The magnetism of EuNi2 P4 is predetermined by Eu 2+ (4f 7 ) with dominant antiferromagnetic interactions. According to the magnetic susceptibility, heat capacity and resistivity measurements, EuNi2 P4 undergoes three phase transitions at ∼2.5 K, 6.1 K and 11.3 K in zero magnetic field.